1990
DOI: 10.3109/10826089009056199
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Smoking in 7- to 9-Year-Old Children

Abstract: This study reports the results of a survey on smoking of 214 children aged 7 to 9 years and 182 children aged 15 to 17 years. It was found that 27.1% of the younger group and 79.5% of the older group had tried to smoke a cigarette (even if just a few puffs). The frequency of continued smoking, as expected, was much greater for the older group, with 55.1% of older smokers compared to 0.9% of younger smokers having puffed during the last 4 weeks. The attitudes of subjects to smoking were generally negative altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…A similar result from the investigation by Yang et al [15] revealed that there tended to be a higher percentage of betel nut chewers who smoked and drank. An intergenerational effect of parental behavior on adolescent students concerning betel nut chewing was observed, and it was very similar to other behavior such as drug abuse, cigarette smoking, and alcohol consumption [17][18][19][20][21][22]. It is said that the intergenerational effect could lead adolescents to use or even abuse these substances.…”
Section: Discussionmentioning
confidence: 95%
“…A similar result from the investigation by Yang et al [15] revealed that there tended to be a higher percentage of betel nut chewers who smoked and drank. An intergenerational effect of parental behavior on adolescent students concerning betel nut chewing was observed, and it was very similar to other behavior such as drug abuse, cigarette smoking, and alcohol consumption [17][18][19][20][21][22]. It is said that the intergenerational effect could lead adolescents to use or even abuse these substances.…”
Section: Discussionmentioning
confidence: 95%
“…There is also a long history of using affect (like/dislike) measures in investigating the possible impact of advertising on children (e.g., Goldberg and Gom 1974;Gorn and Florsheim 1985;Oei and Burton 1990;Wells 1965). Several other responses, such as intent to use, good or bad for you, and perceived risk and harm associated with product use, which may influence future behavior toward a product, were also tested.…”
Section: Affect/attitude Judgmentmentioning
confidence: 99%
“…Communication problems, not only between parent and child, but often between parents as well, characterize the families of substance users (Kandel, Kessler, & Margulies, 1978;Jurich, Polson, Jurich, & Bates, 1985); and the discussion of personal problems with fathers appears to have high potential for discouraging substance use behaviors (Coombs & Paulson, 1988). Youth with a greater tolerance of deviance and more rebellious and delinquent behavior have consistently been found to have higher rates of substance use (Bachman, Johnston, & O'Malley, 1981;Brook et al, 1981Brook et al, , 1983Brook et al, , 1984Guy, Smith, & Bentler, 1994;Jessor, Chase, & Donovan, 1980;Newcomb, 1992;Smith & Fogg, 1979), and liberal attitudes towards substance use are predictive of actual substance use (Fors & Rojek, 1983;O'Connell et al, 1981;Oei & Burton, 1990;Stevens, Youells, Whaley, & Linsey, 1991;Swisher, Shute, & Bibeau, 1984;White, 1991White, , 1993White, , 1995. Poor school performance is often related to use of substances (Bachman et al, 1981;Fors & Rojek, 1983;Guy et al, 1994;Hundleby & Mercer, 1987;Newcomb, 1992;Paulson, Coombs, & Richardson, 1990).…”
Section: Relevant Literature Related To Risk Factorsmentioning
confidence: 99%